Εσωτερικές μεταναστεύσεις στο ύστερο Βυζάντιο (μέσα 13ου - τέλη 14ου αι.) - ΚΟΝΤΟΓΙΑΝΝΟΠΟΥΛΟΥ, Αναστασία (Byzantina Symmeikta, 2017)
This paper intents to investigate the terminology used in Byzantine sources for the description of large scale population movements (migration). It also examines the factors causing migrations, their effects, as well as the social and political role of the migrants in their host regions. The often fragmented and scattered evidence in the available primary sources of the period under examination indicates frequent, as well as large movements of population. These movements involve primarily people who flee war zones or conquered areas in search of a safer region within the borders of the Byzantine State. Apart from population movements triggered by military operations, migrations were also caused by political and religious conflicts, natural disasters, epidemics, economic needs and the imperial initiative. Movements of population caused by enemy attacks were provisional, if these attacks did not result to the permanent conquest of a city or region. If, however, certain regions were irrevocably lost to the enemy, then the migration of the former inhabitants of these regions was permanent. The people who moved to the urban centers of this period were gradually incorporated in the economic and social life of the host areas, contributing thus significantly to a much needed regeneration, especially under the turbulent conditions of the late byzantine period.